Heart Failure: Understanding the Prevalence and Modern Approach of Management (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
With increasing modernization and increased work load. People are suffering with various kinds of cardiovascular issues including, ACS, IHD, Cardiomyopathies and Heart failure. As laymen, it was made us understand that heart failure is when our heart stops pumping blood. So to enhance our take on HF, the prevalence and the etiological factors with compensation mechanism of the body and management approach as well is discussed